Health Service Innovation Strategy of TEFA House of Health Promotion with SWOT Analysis - Sabran, Sabran; Suandana, Iwan Abdi; Sari, Dian Kartika (Indonesian Journal Publisher, 2024)
Teaching Factory (TEFA) House of Health Promotion establishment is to enhance healthcare services and public welfare quality. An in-depth analysis is needed to determine the internal and external factors that could influence the creation of TEFA. This research aimed to analyze the Health Service Innovation Strategy of TEFA House of Health Promotion using SWOT analysis. This research method was qualitative, instrument using questionnaires given to TEFA staff and data analysis conducted using SWOT analysis. The research results were based on the SWOT analysis diagram, indicating that TEFA House of Health Promotion was in quadrant I (aggressive quadrant). The recommended strategy is to develop TEFA as a service provider in the health promotion sector. The management of TEFA must create an effective management organizational structure, design a comprehensive TEFA business plan and strategy, and construct a clear workflow and performance Standard Operating Procedure (SOP). It also required a well-defined management and service governance SOP and a well-structured work program. Extend promotions locally and reach a broader audience by utilizing promotional media. Overall, the proposed service innovation strategies are expected to assist TEFA House of Health Promotion in achieving its goal of enhancing the quality of health services and overall public health.